Polysaccharides from Moroccan Green and Brown Seaweed and Their Derivatives Stimulate Natural Defenses in Olive Tree Leaves - Meriem Aitouguinane; Zainab El Alaoui-Talibi; Halima Rchid; Imen Fendri; Slim Abdelkafi; Mohamed Didi Ould El-Hadj; Zakaria Boual; Pascal Dubessay; Philippe Michaud; Mounir Traïkia; Guillaume Pierre; Cherkaoui El Modafar; et al. (Applied Sciences, 2022)
This study aims to assess for the first time the ability of marine polysaccharides and their derivatives to stimulate natural defenses in olive tree leaves. Alginates, ALSM, and ALCM were isolated from the brown algae Sargassum muticum and Cystoseira myriophylloides, respectively. The OASM and OACM fractions were obtained after radical depolymerization of ALSM and ALCM, respectively. Three sulfated polysaccharides, arabinogalactans (AGB and AGP) and fucoidans (FUCCM) were extracted from the green alga Codium decorticatum and the brown seaweed C. myriophylloides, respectively. The extraction yield of different extracts was in the range of 0.82–32% and the average molecular weight (Mw) varied from 3000 Da to 2173 kDa. The M/G ratios of ALSM and ALCM were 0.87 and 1.12, respectively. FUCCM contained 53% of fucose and 12.83% of sulfates. The AGB and AGP fractions were characterized by the presence of a high degree of sulfation and protein (12–23% (w/w)) and were composed mainly of galactose, glucose, and arabinose. The aqueous saccharide solutions were applied to the leaf discs of the olive tree at 0.5 g/L, 1 g/L, and 2 g/L, for 24 h. These molecules triggered defense responses, by showing a differential capacity to induce the activity of the phenylalanine and tyrosine ammonia-lyase (TAL and PAL), polyphenols, and lignin contents in the leaves of the olive tree. Alginates and their derivatives as well as arabinogalactans exhibited an important induction of TAL activity compared to the PAL. The sulfated polysaccharides were more effective compared to the unsulfated polysaccharides (alginates) which were active at a low concentration. The optimum concentration for most of the studied elicitors was 2 g/L. These results suggest the valorization of these molecules derived from marine biomass as inducers of natural defenses of the olive tree to protect against phytopathogens in the context of sustainable development.